Reducing foreign language anxiety through cooperative learning: Enhancing speaking skills for BIPA learners - Mufti, Mahira Mujahida Ani; Sulistyaningsih, Lilis Siti; Rifkiyanfi, Mochamad Whilky (citeus, 2025)
Indonesia's economic and political development has sparked global interest, contributing to the increasing status of Indonesian as an international language. This has led to a growing number of learners in the BIPA (Bahasa Indonesia for Foreign Speakers) program. While many studies have focused on learning materials, media, models, and evaluation tools, research on foreign language anxiety in the BIPA context remains limited. This study investigates the effectiveness of cooperative strategies in reducing language anxiety and improving speaking skills among BIPA Level 1 students. Using a quantitative Single Subject Research (SSR) method with an A-B-A design, the study involved three purposively selected students at the UPI Language Center. Results indicated that the implementation of cooperative strategies effectively reduced anxiety and enhanced speaking performance. Subject 1 showed an increase from a baseline (A1) average of 57.5 to 82.3 during intervention and 86.5 in the second baseline (A2). Subject 2 improved from 71.5 (A1) to 77 (intervention) and 78.5 (A2). Subject 3's scores rose from 59.5 (A1) to 65.6 (intervention) and 74 (A2). These findings suggest that cooperative strategies are a promising approach to addressing language anxiety and improving speaking skills in BIPA learners.